The Relationship between Child Abuse and the Risk of Suicidal Ideation among Adolescents in Bandung City - Prasetia, Ayu; Saputra, Lucky; Andayani, Santi (Global Medical & Health Communication (GMHC), 2025)
The 2015 United Nations Children's Fund (UNICEF) report stated that violence against children occurs widely in Indonesia, and from the results of monitoring by the Indonesia Child Protection Commission (Komisi Perlindungan Anak Indonesia, KPAI), the increase in the number of violence against children has increased significantly from 2011 to 2015. The impact of violence on children is vast, including the increased risk of suicidal behavior. This research employed a cross-sectional method with adolescents aged 13–18 years in Bandung city. Subject selection was conducted using the consecutive sampling method. The history of violence was measured using the IPSCAN Child Abuse Screening Tool for Children (ICAST-C) Indonesian language version, and the risk of suicide ideation was calculated using the early detection of adolescent suicide ideation risk factors instrument. Data analysis uses the chi-square method and the t-independent test (unpaired). This research was conducted during the COVID-19 pandemic, and the researcher collected data online. The study was conducted in Bandung city. Data collection was carried out from May to June 2020. The results of 69 adolescents in Bandung city were 72% (50 adolescents) who experienced at least 1 type of violence, and 36% (25 adolescents) had suicidal thoughts. Teens who had experienced violence were 16.6 times more likely also to have suicidal ideation. The conclusion was found that there was a meaningful relationship between child abuse and the risk of suicidal ideation in adolescents in Bandung city.